2021
DOI: 10.1002/tpg2.20121
|View full text |Cite
|
Sign up to set email alerts
|

A near‐complete genome sequence of mungbean (Vigna radiata L.) provides key insights into the modern breeding program

Abstract: Mungbean (Vigna radiata L.), a fast-growing legume species, is an important source of carbohydrates and proteins in developing countries of Asia. Here, we constructed a near-complete genome sequence of mungbean with a scaffold N50 value of 5.2 Mb and only a 0.4% gap, with a total scaffold size of 475 Mb. We identified several misassembled pseudomolecules (Chr03, Chr04, Chr05, and Chr08) in the previous draft assembly; Chr03, Chr04, and Chr08 were assembled into one chromosome, and Chr05 was broken into two chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 70 publications
3
53
1
Order By: Relevance
“…Our results showed that another feature of Baekdadagi-specific genetically diverse genomic regions is maintenance of genetic diversity; however, this diversity was not distributed evenly across the cucumber genomes. These results are consistent with selective sweep events which happened during domestication and modern breeding in mung bean and lettuce [38,39]. Putative selective sweep regions of both crops were also not distributed evenly.…”
Section: Discussionsupporting
confidence: 80%
“…Our results showed that another feature of Baekdadagi-specific genetically diverse genomic regions is maintenance of genetic diversity; however, this diversity was not distributed evenly across the cucumber genomes. These results are consistent with selective sweep events which happened during domestication and modern breeding in mung bean and lettuce [38,39]. Putative selective sweep regions of both crops were also not distributed evenly.…”
Section: Discussionsupporting
confidence: 80%
“…The appreciable difference in FreeBayes QV between the two assemblies still points towards a higher error rate in the TGACv2 reference, and suggests that the ARS_RCv1.1 assembly is more suitable as a reference for short-read WGS alignment in the red clover species. The MedTr4 assembly represents a high-quality reference for most legume species, and has been used in several whole genome comparisons to indicate assembly quality [39,40]. This includes the original release of the TGACv2 reference, where synteny was identified between MedTr4 and the TGACv2 assembly [14].…”
Section: Data Validation and Quality Control Assembly Error-rate Asse...mentioning
confidence: 99%
“…The MedTr4 assembly represents a high quality reference for most legume species, and has been used in several whole genome comparisons to indicate assembly quality [31,32]. This includes the original release of the TGACv2 reference, where synteny was identified between MedTr4 and the TGACv2 assembly [14].…”
Section: Data Validation and Quality Controlmentioning
confidence: 99%